Cancer Antigen 125 (CA125, MUC16) Protein Expression in the Diagnosis and Progression of Pancreatic Ductal Adenocarcinoma. Issue 9 (October 2017) - Jiang, Kun; Tan, Elaine; Sayegh, Zena; Centeno, Barbara; Malafa, Mokenge; Coppola, Domenico
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is an aggressive carcinoma, with most patients diagnosed at an advanced stage, with a 5-year survival rate of around 5%. An urgent need exists for identifying better diagnostic, prognostic, and therapeutic markers for this lethal disease. Recently, CA125 has been identified in PDAC, and the aim of this research is to study the changes in CA125 expression during the progression of benign pancreatic tissue (BPT) to PDAC and to assess its value as a biomarker of tumor growth. To address these questions, the cellular levels of CA125 in BPT and PDAC were measured using immunohistochemistry and compared on the basis of tumor staging, and the tissue microarray technology were constructed using resected pancreatic tissues. The staining reactions for each case were evaluated semiquantitatively using the histologic score system. Our investigation demonstrates a consistent and significant upregulation of CA125 during the transition from BPT to PDAC. We also found a direct correlation between CA125 immunohistochemistry score and tumor stage ( P =0.02). In conclusion, our data indicate that CA125 plays a direct role in pancreatic carcinogenesis and suggests that it may eventually be used as a diagnostic and/or prognostic biomarker of pancreatic cancer. Prospective studies are recommended to evaluate further the diagnostic and prognostic capabilities of CA125 in PDAC, and further studies are warranted to assess the use of CA125 as a therapeutic marker.